Research methods for economics - Mishi, Syden; Maredza, Andrew (Pretoria : Van Schaik Publishers, 2024)
For a long time, Economics research and research teaching have concentrated on Econometrics, which has been dominated by the quantitative analysis of secondary data. When Economics graduates enter the world of work and are asked to produce a certain report, the first thing they ask is (3z(Bwhere can I download the data?(3y(B, not knowing how to generate the data themselves. Research methods for economics hopes to build a graduate who will say (3z(Bhow can I generate robust data?(3y (Band (3z(Bhow can I process these data to answer the key questions?(3y(BResearch methods for economics introduces the novice to the world of research, specifically as applied to the discipline of Economics. It starts with what research entails and then branches out into the different approaches, concluding with chapters on how students should write and structure their academic work. The text provides step-by-step examples using different types of case study, data and analytical tools, and is user-friendly for both students and instructors.s
Keywords: Economics$1 (BResearchs -- South Africa